Can Indonesia Become A Cashless Society through Digitalization and Financial Literacy? - Soenjoto, Wening Purbatin Palupi; Mahmudah, Siti Nur (El-Barka Journal of Islamic Economics and Business, 2023)
After the Covid-19 pandemic, it cannot be denied that online shopping has increased shopping behavior patterns using non-cash money. This is due to restrictions on community activities and cash is considered to be a trigger for the spread of the Covid19 virus. This research looks at the phenomenon of using cash as an impact of the Covid-19 pandemic, whether it triggers an increase in non-cash financial literacy and whether government programs for people's movement to use non-cash money can form a non-cash society as a form of effective use of non-cash money or even trigger consumer behavior with minimal understanding non-cash financial literacy. This research uses a qualitative, phenomenal approach by collecting data through interviews with 50 informants with criteria aged 19-21 years and to triangulate the data, interviews were conducted with 2 employees of Bank BSI Jombang and BRI Pulung Ponorogo who have expertise in the banking sector. Based on the research results, it is stated that cashless users aged 19-21 years, influence consumer behavior but have not yet been balanced with detailed knowledge of digital financial literacy and still the function of non-cash money is mostly on shopping behavior so that digital financial skills in non-cash only limited to debits and credits in the cash flow of bank accounts. There is a difference between women and men in usage, namely that men study the products they will buy using cashless and are not easily influenced by promotions compared to women who easily use cashless without studying the details of the products they will buy so they are easily influenced by promotions. It can be used as a basis for policy making in the economic and banking sectors.